Worldwide Status of CCUS Technologies and Their Development and Challenges in China. (28th August 2017) - Liu, H. J.; Were, P.; Li, Q.; Gou, Y.; Hou, Z.
Abstract : Carbon capture, utilization, and storage (CCUS) is a gas injection technology that enables the storage of CO2 underground. The aims are twofold, on one hand to reduce the emissions of CO2 into the atmosphere and on the other hand to increase oil/gas/heat recovery. Different types of CCUS technologies and related engineering projects have a long history of research and operation in the USA. However, in China they have a short development period ca. 10 years. Unlike CO2 capture and CO2 -EOR technologies that are already operating on a commercial scale in China, research into other CCUS technologies is still in its infancy or at the pilot-scale. This paper first reviews the status and development of the different types of CCUS technologies and related engineering projects worldwide. Then it focuses on their developments in China in the last decade. The main research projects, international cooperation, and pilot-scale engineering projects in China are summarized and compared. Finally, the paper examines the challenges and prospects to be experienced through the industrialization of CCUS engineering projects in China. It can be concluded that the CCUS technologies have still large potential in China. It can only be unlocked by overcoming the technical and social challenges.